The fluctuating population of Sm 4f configurations in topological Kondo insulator SmB6 explored with high-resolution X-ray absorption and emission spectra. Issue 35 (23rd August 2017) - Lee, Jenn-Min; Haw, Shu-Chih; Chen, Shi-Wei; Chen, Shin-Ann; Ishii, Hirofumi; Tsuei, Ku-Ding; Hiraoka, Nozomu; Liao, Yen-Fa; Lu, Kueih-Tzu; Chen, Jin-Ming
Abstract : RXES of SmB6 probed at (a) 300 K and (b) 10 K. The decomposed characteristics are drawn in (c). Abstract : High-resolution partial-fluorescence-yield X-ray absorption and resonant X-ray emission spectra were used to characterize the temperature dependence of Sm 4f configurations and orbital/charge degree of freedom in SmB6 . The variation of Sm 4f configurations responds well to the formed Kondo gap, below 140 K, and an in-gap state, below 40 K. The topological in-gap state is correlated with the fluctuating population of Sm 4f configurations that arises via carrier transfer between 3d 9 4f 6 and 3d 9 4f 5 states; both states are partially delocalized, and the mediating 5d orbital plays the role of a transfer path. Complementary results shown in this work thus manifest the importance of configuration fluctuations and orbital delocalization in the topological surface state of SmB6 .